Diseño, Validación y Confiabilidad de un Instrumento Para Medir el Sentido de Pertenencia en Comunidades Virtuales de Intereses (Amino) (2021)
The purpose of this research was to design, validate and determine the reliability of a new instrument to measure the sense of belonging in virtual communities of interest (Amino), under a quantitative methodological framework of cross-sectional-descriptive scope with a nonexperimental design and an empirical-analytical approach. Thus, a psychometric instrument was developed, finally composed of 9 categories and 55 items; which had content and construct validation, in addition to determining its reliability through the halving method, and its internal consistency was estimated through Cronbach's Alpha method, where its respective data analysis was performed after having applied the instrument in a validity pilot test in the Roleplay Escolar Amino and Roleplay [Corazón] Amino communities. From a psychometric perspective, the tool met all the requirements to be considered a valid and reliable instrument